Rancang Bangun Sistem POS (Point of sales) Berbasis Web (Studi kasus: Massimo Parfum) - Wekong , Yoxander Sumantro; Kusuma, Agus Tommy Adi Prawira; Tonyjanto, Christian (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
The development of information technology encourages businesses to improve operational efficiency, including through -based Point of Sales (POS) systems. Massimo Parfum Store still uses manual transaction recording, which is prone to errors and delayed reporting. This study aims to design and develop a -based POS system to support sales transactions, product management, and report generation. The system development uses the Waterfall method, which includes analysis, design, implementation, and testing phases. The system is built using PHP and MySQL, and runs on a local XAMPP server. The result was that a POS system is capable of accurately recording transactions, managing product data, and generating daily, monthly, and yearly sales reports. The system was expected to improve data accuracy, speed up service, and help store owners monitor sales activity in real time.